Predictive Clinical and Surgical Factors Associated with Recurrent Apoplexy in Pituitary Adenomas - Siu, Alan; Rangarajan, Sanjeet; Karsy, Michael; Farrell, Christopher J.; Nyquist, Gurston; Rosen, Marc; Evans, James J. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction Pituitary apoplexy is an uncommon clinical condition that can require urgent surgical intervention, but the factors resulting in recurrent apoplexy remain unclear. The purpose of this study is to determine the risks of a recurrent apoplexy and better understand the goals of surgical treatment.Methods A retrospective chart review was performed for all consecutive patients diagnosed and surgically treated for pituitary apoplexy from 2004 to 2021. Univariate analysis was performed to identify risk factors associated with recurrent apoplexy.Results A total of 115 patients were diagnosed with pituitary apoplexy with 11 patients showing recurrent apoplexy. This occurred at a rate of 2.2 cases per 100 patient-years of follow-up. There were no major differences in demographic factors, such as hypertension or anticoagulation use. There were no differences in tumor locations, cavernous sinus invasion, or tumor volumes (6.84 ± 4.61 vs. 9.15 ± 8.45 cm, p = 0.5). Patients with recurrent apoplexy were less likely to present with headache (27.3%) or ophthalmoplegia (9.1%). Recurrent apoplexy was associated with prior radiation (0.0 vs. 27.3%, p = 0.0001) and prior subtotal resection (10.6 vs. 90.9%, p = 0.0001) compared with first time apoplexy. The mean time to recurrent apoplexy was 48.3 ± 76.9 months and no differences in overall follow-up were seen in this group.Conclusion Recurrent pituitary apoplexy represents a rare event with limited understanding of pathophysiology. Prior STR and radiation treatment are associated with an increased risk. The relatively long time from the first apoplectic event to a recurrence suggests long-term patient follow-up is necessary.
Keywords: pituitary adenoma; apoplexy; endoscopic; recurrent hemorrhage; radiation